Comércio internacional e integraç\~ao produtiva: Uma análise dos fluxos comerciais dos países da ALADI - Marta Castilho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– Despite the strong growth of the Latin American foreign trade in the 2000s, the integration of these countries in the global production and trade networks is relatively weak, what largely reflects these countries' specialization on goods intensive in natural resources. In general, the share of capital goods and intermediate goods, particularly, parts and components, in Aladi total trade is small, which reveals a low participation of these countries in global production chains. These goods are more important in imports than in exports, evidencing that their low integration is, furthermore, characterized by the consumption of these goods in order to product or assembly final goods targeted to internal or external markets. The indicators of the share of parts, components and capital goods in intra-regional trade, although higher than in extra-regional trade, evidence a low regional production integration. They suggest the existence of an incipient productive articulation between the Aladi countries that is incomparably weaker than that observed in Asian countries and that seems insufficient to strengthen the international competitiveness of the goods made in Aladi.
Keywords: F14; F15; 330; Internationale Wirtschaftsbeziehungen; Lateinamerika